Ado-trastuzumab emtansine – The monoclonal drug conjugate in human epidermal growth factor receptor 2-positive breast cancer - Sandip Ganguly; Joydeep Ghosh; Bivas Biswas; Deepak Dabkara (Indian Journal of Medical and Paediatric Oncology)
Human epidermal growth factor receptor 2 (HER2)-positive breast cancer comprises around 20%–25% of breast cancers. With the discovery of trastuzumab, there was a marked improvement in the survival of patients with HER2-positive breast cancer both in curative and metastatic settings. However, patients with trastuzumab will eventually progress or develop recurrences. Newer anti-HER2 therapies have evolved to improve the outcome of this group of patients. One of them is monoclonal antibody–drug conjugate which is ado-trastuzumab emtansine.